2005
DOI: 10.1007/s00059-005-2685-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Simvastatin Therapy after Heart Transplantation

Abstract: Statin therapy initiated in heart transplant patients early in the postoperative period plays an important role for better survival and lower incidence of transplant vasculopathy. The 11-year results of this study implicate that each heart transplant patient should receive early treatment with a statin as a matter of routine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 4 publications
1
18
0
1
Order By: Relevance
“…These effects have been attributed to disruption of small GTP-binding proteins in the Ras superfamily, which derive their important post-translational isoprenoid modifications from the cholesterol biosynthesis pathway. [6][7][8][9] Therapeutic statin-mediated immunomodulatory activity has been demonstrated in animal models of asthma and sepsis. [10][11][12][13][14][15][16][17] Specifically, statins have been reported to improve survival in the cecal-ligation and puncture (CLP) and lipopolysaccharide (LPS)-injection models of sepsis.…”
Section: Introductonmentioning
confidence: 99%
“…These effects have been attributed to disruption of small GTP-binding proteins in the Ras superfamily, which derive their important post-translational isoprenoid modifications from the cholesterol biosynthesis pathway. [6][7][8][9] Therapeutic statin-mediated immunomodulatory activity has been demonstrated in animal models of asthma and sepsis. [10][11][12][13][14][15][16][17] Specifically, statins have been reported to improve survival in the cecal-ligation and puncture (CLP) and lipopolysaccharide (LPS)-injection models of sepsis.…”
Section: Introductonmentioning
confidence: 99%
“…Additionally, statin use in heart transplant patients is associated with improved cardiac allograft vasculopathy in both adults [146] and children [147]. These results were also verified in a long-term (11 years) evaluation study of heart transplant patients [148]. The incidence of graft coronary vasculopathy confirmed by angiography was 34.6% vs. 73.9%, in the simvastatin and placebo groups, respectively (P < 0.01).…”
Section: C) Statins and Transplantationmentioning
confidence: 53%
“…The results of 4-, 8-, and 11-year follow-up studies of heart transplant patients by Wenke et al [85][86][87] are also interesting. The authors found, after an 11-year of follow-up, a 77% survival rate in the simvastatin group, as compared to 56.8% (p<0.05) in the control cohort.…”
Section: Use Of Statins In Transplantation Medicinementioning
confidence: 91%